Comparison of thyroid hormone status between pre-eclampsia and normotensive pregnancy after 37 weeks - Aravazhi, Mahalakshmi; Ajit, Rashmi; Breetha, V.; Sruthi, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preeclampsia is the leading cause of maternal mortality in developing countries and is associated with a fivefold increase in perinatal mortality. The mechanism of hypothyroidism in pre-eclampsia is controversial and may be related to decreased plasma protein concentrations and increased endothelin levels. Methods: This was a prospective comparative study in 100 women; out of them, 50 were normal pregnant women in the control group and 50 preeclamptic women in the case group. Thyroid hormones, total FT3, FT4 and TSH were analyzed in these subjects. The cases of pre-eclampsia characterized by elevation of blood pressure of more than 140 mmHg systolic or more than 90 mmHg diastolic with proteinuria (more than 300 mg/l in 24 hours specimen) after 37 weeks of gestation in previously normotensive nonproteinuric pregnant women. Results: Incidence of hypothyroidism is high in the study group (30%) compared to the control (14%). Furthermore, the maximum subjects were observed with euthyroidism 43 (86%) in the control group, whereas subclinical hypothyroidism 23 (46%) was observed highest in the preeclamptic group. Out of the 50 preeclamptic patients, 13 (26%) belonged to the severe whereas 37 (74%) belonged to the mild pre-eclampsia group. Conclusions: The study concluded that the pre-eclamptics have a higher incidence of hypothyroidism (SCH) in contrast to the normotensive women, and there is a correlation between the severity of pre-eclampsia and hypothyroidism.